The mechanochemical synthesis of quinazolin-4(3H)-ones by controlling the reactivity of IBX - Alam, Md Toufique; Maiti, Saikat; Mal, Prasenjit (Beilstein Journal of Organic Chemistry, 2018)
Performing any synthesis using several arylamines and hypervalent iodine(V) reagents by direct mixing is unrealistic because of the high exothermic reaction or explosion. Herein we demonstrate, when anilines were substituted with an amide group at the ortho-position, successful chemical reactions could be performed due to intramolecular control. At maximum contact of the reacting substances, i.e., under solvent-free mechanochemical conditions, 2-aminobenzamides, aryl-, alkylaldehydes and the iodine(V) reagent o-iodoxybenzoic acid (IBX) led to substituted quinazolin-4(3H)-one derivatives in fair yields.
Keywords: ball-mill; contact explosive; IBX; mechanochemical synthesis; quinazolin-4(3H)-one

(untitled) - Tornieporth-Oetting, I.; Klapötke, T. (Angew. Chem., Int. Ed. Engl., 1990)

(untitled) - Nicolaou, K. C.; Baran, P. S.; Kranich, R.; Zhong, Y.-L.; Sugita, K.; Zou, N. (Angew. Chem., Int. Ed., 2001)

(untitled) - Hassel, O. (Science, 1970)

(untitled) - Dauban, P.; Dodd, R. H. (Synlett, 2003)

Hypervalent Iodine Chemistry - Zhdankin, V. V. (Preparation, Structure and Properties of Polyvalent Iodine Compounds, 2013)

(untitled) - Zhdankin, V. V.; Stang, P. J. (Chem. Rev., 2008)

(untitled) - Achar, T. K.; Bose, A.; Mal, P. (Beilstein J. Org. Chem., 2017)

(untitled) - Prasad, V.; Kale, R. R.; Mishra, B. B.; Kumar, D.; Tiwari, V. K. (Org. Lett., 2012)

(untitled) - Achar, T. K.; Mal, P. (Adv. Synth. Catal., 2015)

(untitled) - Yoshimura, A.; Zhdankin, V. V. (Chem. Rev., 2016)

(untitled) - Muñiz, K. (Top. Curr. Chem., 2015)

(untitled) - Dohi, T.; Kita, Y. (Top. Curr. Chem., 2016)

(untitled) - French, A. N.; Bissmire, S.; Wirth, T. (Chem. Soc. Rev., 2004)

(untitled) - Pellissier, H. (Beilstein J. Org. Chem., 2018)

(untitled) - Sharma, P.; Kaur, N.; Pareek, A.; Kishore, D. (Sci. Rev. Chem. Commun., 2013)

(untitled) - Duschek, A.; Kirsch, S. F. (Chem. – Eur. J., 2009)

(untitled) - Richardson, R. D.; Zayed, J. M.; Altermann, S.; Smith, D.; Wirth, T. (Angew. Chem., Int. Ed., 2007)

(untitled) - Singh, F. V.; Wirth, T. (Synthesis, 2013)

(untitled) - Yusubov, M. S.; Zhdankin, V. V. (Curr. Org. Synth., 2012)

(untitled) - Ladziata, U.; Zhdankin, V. V. (ARKIVOC, 2006)

(untitled) - Maiti, S.; Mal, P. (J. Org. Chem., 2018)

(untitled) - Maiti, S.; Bose, A.; Mal, P. (J. Org. Chem., 2018)

(untitled) - Maiti, S.; Alam, M. T.; Mal, P. (Asian J. Org. Chem., 2018)

(untitled) - Maiti, S.; Mal, P. (Org. Lett., 2017)

(untitled) - Maiti, S.; Achar, T. K.; Mal, P. (Org. Lett., 2017)

(untitled) - Maiti, S.; Mal, P. (Adv. Synth. Catal., 2015)

(untitled) - Lee, J. B.; Kang, M. E.; Kim, J.; Lee, C. Y.; Kee, J.-M.; Myung, K.; Park, J.-U.; Hong, S. Y. (Chem. Commun., 2017)

(untitled) - Parua, S.; Das, S.; Sikari, R.; Sinha, S.; Paul, N. D. (J. Org. Chem., 2017)

(untitled) - Achar, T. K.; Maiti, S.; Mal, P. (RSC Adv., 2014)

(untitled) - Hernández, J. G.; Bolm, C. (J. Org. Chem., 2017)

(untitled) - James, S. L.; Adams, C. J.; Bolm, C.; Braga, D.; Collier, P.; Friščić, T.; Grepioni, F.; Harris, K. D. M.; Hyett, G.; Jones, W.; Krebs, A.; Mack, J.; et al. (Chem. Soc. Rev., 2012)

(untitled) - Thorwirth, R.; Bernhardt, F.; Stolle, A.; Ondruschka, B.; Asghari, J. (Chem. – Eur. J., 2010)

(untitled) - Thottumkara, A. P.; Bowsher, M. S.; Vinod, T. K. (Org. Lett., 2005)

(untitled) - Weng, Y.; Lan, T.; Sun, C.; Yang, T.; Su, W.; Xie, Y. (Org. Chem. Front., 2018)

(untitled) - Cheng, R.; Guo, T.; Zhang-Negrerie, D.; Du, Y.; Zhao, K. (Synthesis, 2013)

(untitled) - Hati, S.; Sen, S. (Synthesis, 2016)

(untitled) - Frigerio, M.; Santagostino, M.; Sputore, S. (J. Org. Chem., 1999)